A comparative study of salivary and serum iron in normal and anaemic female patients in Udaipur city, Rajasthan, India - Mantu, Vinayak Kumar; Mitra, Ruchi; Mitra, Jeewan Kumar (Archives of Oral Research, 2013)
Objective: To evaluate the concentration of serum iron and salivary iron in anemic and normal female patients and to compare and correlate the concentration of serum and salivary iron. Material and methods: The 20 Anemic and 20 non-anemic as control group female patients of age groups of 20-40 yrs were included in the study. Unstimulated whole saliva was collected and the morning blood sample was collected simultaneously. Salivary and serum iron was determined using automatic analyzer by Ferrozine method. Results: The salivary iron was significantly high in anemic female patients as compared to controls. The mean salivary:serum iron ratio was four times in anemic females as compared to control group. The correlation between salivary iron and serum iron was (p<0.05) in these cases. Conclusion: The iron in saliva is maintained at a higher level in iron deficiency anemia and it correlates well with serum iron in iron deficient anemic patients.